Survival of Lactobacillus acidophilus NCFM® and Bifidobacterium lactis HN019 encapsulated in chocolate during in vitro simulated passage of the upper gastrointestinal tract. (December 2016) - Klindt-Toldam, Stine; Larsen, Susanne K.; Saaby, Lasse; Olsen, Louise R.; Svenstrup, Gitte; Müllertz, Anette; Knøchel, Susanne; Heimdal, Hanne; Nielsen, Dennis S.; Zielińska, Dorota
Abstract: Probiotic microorganisms are exposed to different types of stress both before and after consumption which strongly influences probiotic survival. Here the viability of 2 different probiotic bacteria incorporated in different types of chocolate was investigated during storage and passage of the upper gastro-intestinal tract using both a static and a dynamic gastric in vitro model. Lactobacillus acidophilus NCFM ® and Bifidobacterium lactis HN019 equalling a total concentration of 2 × 10 8, 2 × 10 9 and 2 × 10 10 CFU/g chocolate were added to samples of milk chocolate, 57% and 72% dark chocolate, respectively. The probiotic strains tolerated the manufacturing process reasonable well with a reduction of 1.1–1.6 log CFU/g after one month of storage, and showed an excellent survivability during 14 months of storage, especially when kept at a constant temperature of 15 °C. In comparison with commercial dairy and juice based probiotic products, chocolate was an excellent carrier for probiotic delivery, because of very good survival of probiotics during simulated passage of the upper GI tract. The viability of B. lactis was slightly higher than Lb. acidophilus and survival rates were >6.5 log CFU/g in case of the static, and >7.0 log CFU/g, in case of the dynamic gastric model, with milk chocolate being the most protective carrier. Highlights: Chocolate containing high numbers of probiotic bacteria can easily be produced. The Dynamic Gastric Model is a tool well suited for investigating the probiotic incorporated in food. Chocolate is a good carrier of probiotics. Chocolate preserves viability of probiotic bacteria during digestion.